Two-dimensional soft supramolecular networks. Issue 97 (14th October 2015) - Palma, Carlos-Andres; Ciesielski, Artur; Öner, Murat Anil; Schaeffer, Gaël; Lehn, Jean-Marie; Barth, Johannes V.; Samorì, Paolo
Abstract : Soft networks are self-assembled at the solid/liquid interface and characterized by local disorder arising from multivalent flexible intermolecular interactions. Abstract : Two flexible multivalent molecular units are employed to self-assemble highly regular supramolecular porous networks at the solid/liquid interface. Scanning tunnelling microscopy imaging corroborated with molecular dynamics simulations make it possible to elucidate the conformational freedom behind the binding motif, which identify the architecture as a highly regular soft network.